Implementation of Learning During the Covid-19 Pandemic in Economic Subjects in High Schools - Rahmawati, Yuntafiani Mufidatu; Hakim, Lukman; Murwaningsih, Tri (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2021)
This research uses a descriptive qualitative approach. The data in this study are primary data and secondary data. The data collection techniques used were observation, documentation and interviews. The validity test in this study uses four validation criteria that must be met, namely 1) credibility, 2) transferability, 3) dependability, and 4) confirmability. This study aims to determine the results of the implementation of learning during the Covid-19 pandemic in economic subjects in high schools which are guided by pandemic conditions which cause changes in face-to-face learning patterns to online-based learning. The conclusion obtained, 97% of the implementation of learning economic subjects is done online. 75.9% of teachers prefer to use google class as a learning platform that helps teachers deliver material to students. Meanwhile, for miling list media such as WhatsApp, it was assessed that 75.9% of teachers were more effective in communicating with students. The implementation of online learning makes the teacher adapt to the situation, makes learning plans that are implemented based on existing conditions, the teacher must schedule learning, the teacher must prepare learning materials that make it easier for students to learn.